The gut microbiome distinguishes mortality in trauma patients upon admission to the emergency department. Issue 5 (May 2020) - Burmeister, David M.; Johnson, Taylor R.; Lai, Zhao; Scroggins, Shannon R.; DeRosa, Mark; Jonas, Rachelle B.; Zhu, Caroline; Scherer, Elizabeth; Stewart, Ronald M.; Schwacha, Martin G.; Jenkins, Donald H.; Eastridge, Brian J.; et al.
Abstract : BACKGROUND: Traumatic injury can lead to a compromised intestinal epithelial barrier, decreased gut perfusion, and inflammation. While recent studies indicate that the gut microbiome (GM) is altered early following traumatic injury, the impact of GM changes on clinical outcomes remains unknown. Our objective of this follow-up study was to determine if the GM is associated with clinical outcomes in critically injured patients. METHODS: We conducted a prospective, observational study in adult patients (N = 67) sustaining severe injury admitted to a level I trauma center. Fecal specimens were collected on admission to the emergency department, and microbial DNA from all samples was analyzed using the Quantitative Insights Into Microbial Ecology pipeline and compared against the Greengenes database. α-Diversity and β-diversity were estimated using the observed species metrics and analyzed with t tests and permutational analysis of variance for overall significance, with post hoc pairwise analyses. RESULTS: Our patient population consisted of 63% males with a mean age of 44 years. Seventy-eight percent of the patients suffered blunt trauma with 22% undergoing penetrating injuries. The mean body mass index was 26.9 kg/m 2 . Significant differences in admission β-diversity were noted by hospital length of stay, intensive care unit hospital length of stay, number of days on the ventilator, infections, and acute respiratory distress syndrome ( p < 0.05). β-Diversity on admission differed in patients who died compared with patients who lived (mean time to death, 8 days). There were also significantly less operational taxonomic units in samples from patients who died versus those who survived. A number of species were enriched in the GM of injured patients who died, which included some traditionally probiotic species such as Akkermansia muciniphilia, Oxalobacter formigene s, and Eubacterium biforme ( p < 0.05). CONCLUSION: Gut microbiome diversity on admission in severely injured patients is predictive of a variety of clinically important outcomes. While our study does not address causality, the GM of trauma patients may provide valuable diagnostic and therapeutic targets for the care of injured patients. LEVEL OF EVIDENCE: Prognostic and epidemiological, level III. Abstract : Supplemental digital content is available in the text.